On the anomalous susceptibility of small gap magnetic semiconductors (SmS, SmSe, SmTe). - Balseiro, Carlos Antonio; Passeggi, M. C.; Alascio, Blas Rafael (1975)
Fil: Balseiro, C. A. Comisión Nacional de Energía Atómica; Argentina